Freedom of Contract in Consumer Transactions and Its Effect on Consumer Protection - Rusli, Benni (Asosiasi Ide Bahasa Kepri, 2023)
This research aims to reveal the Freedom of Contract in Consumer Transactions and its Influence on Consumer Protection. The application of the principle of freedom of contract in consumer transactions can influence efforts to provide adequate legal protection to consumers, who are often considered to be in a weak position in every transaction carried out with business actors or producers. Freedom of contract in consumer transactions has been adequately regulated and guaranteed in applicable laws and regulations, both in the Consumer Protection Law, the Civil Code and other provisions. Meanwhile, factors that can influence the application of freedom of contract include agreement standards or contract standards used in consumer transactions, actions that support conditions in the process of making agreements/contracts in consumer transactions, the principle of balance in the contents of agreements/contracts in consumer transactions and incompatibility of fair doctrine and inappropriate influence in the preparation of agreements/contracts in consumer transactions. The research method used was a qualitative method with systematic steps and a normative analysis method. The results of this research show 4 main things, namely the Principle of Freedom of Contract in Agreements or Contracts, Consumer Protection, Protection of Consumers in Agreements, and The Implementation of the Principle of Balance in Consumer Transactions.